2018
DOI: 10.1016/j.ajoc.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

MRI visualization of optic nerve avulsion due to ocular perforation from BB gun projectile

Abstract: To report a case of optic nerve avulsion after a perforating injury by an air-soft/BB gun that was successfully captured with magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…MRI detection of ONA is uncommon because optic nerve dural sheaths typically remain attached to the globe, making detection difficult. Barnard and Ajlan 29 described the significance of MRI in identifying ONA after Ball Bearing (BB) gun trauma. They demonstrated that MRI is essential when there is no obvious cause for visual loss following trauma or when conventional ophthalmic diagnostic techniques, such as B-scan ultrasonography, are unable to detect ONA.…”
Section: Discussionmentioning
confidence: 99%
“…MRI detection of ONA is uncommon because optic nerve dural sheaths typically remain attached to the globe, making detection difficult. Barnard and Ajlan 29 described the significance of MRI in identifying ONA after Ball Bearing (BB) gun trauma. They demonstrated that MRI is essential when there is no obvious cause for visual loss following trauma or when conventional ophthalmic diagnostic techniques, such as B-scan ultrasonography, are unable to detect ONA.…”
Section: Discussionmentioning
confidence: 99%
“…24 • Hypo-intensities in the posterior globe. 13 • Tearing of the left optic nerve distal to the optic chiasma. High diffusionweighted imaging (DWI) signal of the optic chiasma to the optic tract indicated nerve injury.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%